Study to detect cytotoxicity of The eggplant plant ( Solanum melongena L) - Ahlam Husain Farhoud Khalawi (University of Thi-Qar Journal of agricultural research, 2022)
The current study included the cytotoxicity test of the active compounds isolated from the peels of the fruits of the eggplant plant, which is found in the local markets of Dhi Qar governorate and used for food and grown within the governorate and not imported during the period (July, August, September, October, November, December. January), the trend of human red blood cells for the purpose of determining the possibility of using them as drug alternatives in the future.The peels of the eggplant plant were extracted with hexane once, then the alkaloid extract was prepared from it again. The alkaloid compounds were detected using the Drankcroff reagent and Mayer's reagent. The positive result of the detection gave an indication of the presence of alkaloid substances that are antioxidants and have a high nutritional value.The concentrations of plant extracts represented by hexane eggplant extract and its alkaloid extract at concentrations (75,50,25,10,5,100) mg/ml were prepared using DMSO solution as a solvent, and a negative control factor containing physiological salt and blood, and a positive control factor (tap water) were prepared. ), and a third control factor consisted of blood solution with DMSO solvent, and the solution was monitored for (3-24) hours to observe the dissolution of blood cells.The cytotoxicity results of plant extracts of Solanum melongena L. showed that the concentrations (75,50,25,10,5,100) mg/ml did not cause any hemolytic and therefore do not cause any cytotoxicity towards red blood cells, and the bottom layer appeared in red color Which represents human blood, and the upper layer represents the extract as well as the physiological solution. If these compounds were toxic, the decomposition of red blood cells would result. Room temperature is 30°C and inside the incubator is 27°C. Incubator made by Dander, Germany and the concentration of the substance.